Development of Explosive Strength in the Representative High School Volleyball Team - E.L. Amzar; L. Rada; I.I. Niculescu (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
The physical education teacher has the obligation to form the representative team of the school unit to be enrolled in the competition provided in the sports calendar, respectively the National School Sports Olympiad. The aim is to educate all students in sports according to their skills, material basis, sports tradition of the educational unit, in order to lay the foundation for the creating the habit of systematic practice of some sports branches, namely the game of volleyball. Motor skills are absolutely necessary for a total participation of the student in all phases of attack and defense. Among these, the value of the motor quality, force, depends on the degree of training and applied efforts, efforts that must be large enough to lead to the development of the student’s moto qualities. Starting from the knowledge of morpho - functional peculiarities specific to the post-pubertal age, a pattern can be structured to identify the optimal solutions for the development of explosive force by general means but also specific to the game of volleyball. The efficiency and diversification strategies of stimulation and development of explosive force in volleyball play involve valuing the theoretical and practical knowledge and experience of the specialist, whose ultimate goal is to discover and capitalize the motor potential of high school students in order to achieve performance in school competitions.